2021
DOI: 10.3847/1538-4357/ac0e91
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Neutrino Mass by Combining Matter Clustering, Halos, and Voids

Abstract: We quantify the information content of the nonlinear matter power spectrum, the halo mass function, and the void size function, using the Quijote N-body simulations. We find that these three statistics exhibit very different degeneracies among the cosmological parameters, and thus the combination of all three probes enables the breaking of degeneracies, in turn yielding remarkably tight constraints. We perform a Fisher analysis using the full covariance matrix, including all auto- and cross correlations, findi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 112 publications
1
45
0
Order By: Relevance
“…However, we do not know what estimator would allow us to extract the maximum amount of information for non-Gaussian density fields, such as the matter and galaxy distribution on nonlinear scales. Quantifying the information content from different estimators is currently a very active area of research (Coulton et al 2019;Li et al 2019;Marques et al 2019;Ajani et al 2020;Allys et al 2020;Banerjee et al 2020;Dai et al 2020;de la Bella et al 2021;Friedrich et al 2020;Giri & Smith 2020;Hahn et al 2020;Villaescusa-Navarro et al 2020;Uhlemann et al 2020;Zhang et al 2020;Banerjee & Abel 2021aBayer et al 2021aBayer et al , 2021bCheng and Ménard 2021;Gualdi et al 2021aGualdi et al , 2021bHahn & Villaescusa-Navarro 2021;Harnois-Déraps et al 2021;Kuruvilla 2021;Kuruvilla & Aghanim 2021;Massara et al 2021;Naidoo et al 2021;Porth et al 2021;Samushia et al 2021;Valogiannis & Dvorkin 2021;Harnois-Déraps et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, we do not know what estimator would allow us to extract the maximum amount of information for non-Gaussian density fields, such as the matter and galaxy distribution on nonlinear scales. Quantifying the information content from different estimators is currently a very active area of research (Coulton et al 2019;Li et al 2019;Marques et al 2019;Ajani et al 2020;Allys et al 2020;Banerjee et al 2020;Dai et al 2020;de la Bella et al 2021;Friedrich et al 2020;Giri & Smith 2020;Hahn et al 2020;Villaescusa-Navarro et al 2020;Uhlemann et al 2020;Zhang et al 2020;Banerjee & Abel 2021aBayer et al 2021aBayer et al , 2021bCheng and Ménard 2021;Gualdi et al 2021aGualdi et al , 2021bHahn & Villaescusa-Navarro 2021;Harnois-Déraps et al 2021;Kuruvilla 2021;Kuruvilla & Aghanim 2021;Massara et al 2021;Naidoo et al 2021;Porth et al 2021;Samushia et al 2021;Valogiannis & Dvorkin 2021;Harnois-Déraps et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that extracting information using the power spectrum in this regime is suboptimal (e.g. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
mentioning
confidence: 99%

Multifield Cosmology with Artificial Intelligence

Villaescusa-Navarro,
Anglés-Alcázar,
Genel
et al. 2021
Preprint
Self Cite
“…Recent analyses with alternative approaches like the marked power spectrum and the wavelet scattering transform (hereafter WST) were employed on the very same sets of simulations and of cosmological parameters in Massara et al (2021) and Valogiannis & Dvorkin (2021) respectively. Alternatively, Bayer et al (2021) propose an analysis using the information from the halo mass function (HMF) and the void size function (VSF) in real space. All three analyses, together with ours, consider a maximum scale of k max = 0.5 h/Mpc and can hence be naturally compared.…”
Section: Discussionmentioning
confidence: 99%
“…The information contained in the power spectra bins in cosmic web environments provides the tightest constraints on Ω m , Ω b , h, and n s , and competitive values for constraints on M ν and σ 8 which are however both best constrained by the coefficients derived from the WST. Compared to the partial information of extreme environments from voids and nodes performed in Bayer et al (2021), our environment-dependent statistics are able to tighten the constraints with improvement factors of {0.5, 4.1, 2.9, 3.1, 1.4, 1.7} on the parameters {Ω m , Ω b , h, n s , σ 8 , M ν }, hence performing better than the VSF+HMF statistic in all cases, except for Ω m . These comparisons should however be nuanced in multiple aspects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation